The Implementation of Storynory Audiobook in Teaching Reading Narrative Text - Aiko Putri Tsany (Publikasi Indonesia, 2021)
Background: Reading is one of the crucial components of language learning. However, to understand the whole text in an interesting method, the teacher should provide learning media for students to enjoy while in a serious situation when reading a text. The Audiobook is a tool to read stories or text accompanied by audio recording. Objective: To find out the implementation and response of students in reading narrative texts while listening to audiobooks in their learning activities Methods: Using a qualitative method, with research data collection using observation and interview methods Results: This shows that the application of Storynory audiobooks is easy to apply in the classroom, students can understand narrative texts when using audiobooks. Responses from students and teachers indicate that they enjoy and are satisfied with learning using audiobooks. Conclusion: The application of Storynory audiobooks in teaching narrative text reading shows good responses from students and teachers, they enjoy and easily understand the text, and Storynory audiobooks can help students with their pronunciation of words. did not know before, students enjoy the learning process by using audiobook media. They can repeat the pronunciations they hear in the audio, meaning that audiobooks can introduce and improve students' vocabulary or unfamiliar words in the text.